ChemInform Abstract: Development of a Ruthenium/Phosphite Catalyst System for Domino Hydroformylation‐Reduction of Olefins with Carbon Dioxide. Issue 50 (16th December 2014) - Liu, Qiang; Wu, Lipeng; Fleischer, Ivana; Selent, Detlef; Franke, Robert; Jackstell, Ralf; Beller, Matthias
Abstract The Ru3(CO)12/phosphite‐catalyzed hydroformylation of alkenes is demonstrated for the first time using a mixture of carbon dioxide and hydrogen as reagents.